English language interventions that improve international business student group-work performance - Alexander, P.; Dooey, Patricia (2016)
© 2017 by IGI Global.English-taught business degrees now represent an important part of the global education market. These attract students from all parts of the world, many whose first language is not English. Universities hosting these courses have developed language support mechanisms and programmes which have proven effective in supporting language needs in the academic context. However, these have not generally included specialised attention to group-work where the demands for communicating in English may be significantly more challenging than in a classroom environment. In this chapter, the authors consider the growth of English language support mechanisms in general, and outline a study that quantifies the impact of English in group work performance. They also detail the design of a short intervention programme focused on group-work that can improve the skills learned by students with English as a second language, and increase their performance significantly. They use this study to suggest mechanisms, and to propose improvements to English support programmes.